2017
DOI: 10.1111/hdi.12590
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy on short‐daily home hemodialysis using low dialysate flow rate: A new hope for the end‐stage renal disease patients

Abstract: Short-daily hemodialysis using low dialysate flow rate during pregnancy seems to allow a good control of uremia and blood pressure without requiring a major increase of weekly dialysis duration. Therefore, it could become an alternative to other hemodialysis programs while allowing the patients to continue their treatment at home. However, other studies are necessary in order to define the position of this procedure during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…The second issue, regarding the difficulty in implementing the long, daily dialysis schedules, is also open; this is of utmost importance in developing countries, such as Mexico, where intensive dialysis may lead to a competition for a lifesaving treatment [ 92 ]. Shorter dialysis schedules and peritoneal dialysis are reported as alternatives, but publication bias is an important limit to assess the real equivalence of these more easily manageable treatments [ 128 , 129 , 130 , 131 , 132 ]…”
Section: Dialysismentioning
confidence: 99%
“…The second issue, regarding the difficulty in implementing the long, daily dialysis schedules, is also open; this is of utmost importance in developing countries, such as Mexico, where intensive dialysis may lead to a competition for a lifesaving treatment [ 92 ]. Shorter dialysis schedules and peritoneal dialysis are reported as alternatives, but publication bias is an important limit to assess the real equivalence of these more easily manageable treatments [ 128 , 129 , 130 , 131 , 132 ]…”
Section: Dialysismentioning
confidence: 99%
“…Although there are case reports and case series reporting pregnancies on home dialysis, little is known about pregnancy rates. 11 , 12 , 14 A recent study showed a higher pregnancy rate of 17 PTPY in women with end-stage kidney disease undergoing dialysis; however, this included women on any dialysis modality, with the majority of them getting in-center hemodialysis. 23 Oliverio et al.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 , 10 Existing estimates for home dialysis pregnancies are likely biased from experienced centers and mostly rely on case reports, case series, voluntary surveys, or single-center studies. 11 , 12 , 13 , 14 In addition, the small number of cases precludes our understanding of the factors associated with the likelihood of pregnancy on home dialysis. With the increase in the use of home-based dialysis therapies in the United States and an increasing focus on women’s health, closing this critical knowledge gap becomes particularly important for clinicians and policymakers to help with preconception counseling, shared decision-making, and inform treatment decisions during pregnancy.…”
mentioning
confidence: 99%
“…Home hemodialysis has been shown to decrease mortality and morbidity of patients compared with in-clinic hemodialysis because they are able to use a lower-frequency ultrafiltration rate more often. This reduces the gap between dialysis treatments and reduces cardiac stress [ 10 ].…”
Section: Discussionmentioning
confidence: 99%